Pedagogical Calling as an Experience of Value - Kavaliauskienė, Vanda (Acta Paedagogica Vilnensia, 1997)
The article deals with the problem of pedagogical calling. Pedagogical calling is associated with personal maturity and self-realization in professional realm. While stressing that the description of pedagogical calling as a psychological feature of personality, covering motivation, potency and character is insufficient, the article emphasizes the value aspect of pedagogical calling. Analysing the expression of pedagogical calling as the experience of the value, importance of wisdom and conduct is especially emphasized – experience of pedagogical calling as a value is only possible through the wise educational activity oriented towards the good.
Keywords: values; teacher; pedagogical calling; personal maturity; self-realization